Traffic Condition Information Extraction & Visualization from Social Media Twitter for Android Mobile Application - Endarnoto, S. K.; Pradipta, S.; Nugroho, A. S.; Purnama, J. (Proceedings of the 2011 International Conference on Electrical Engineering and Informatics, 2011)
Traffic jam in Jakarta, Indonesia has become a crucial problem for the society. A Traffic Management Center has been built by the police, in this case Polda Metro Jaya to help people to get the latest information regarding traffic jam. Twitter has been used by TMC Polda Metro Jaya to spread the news of traffic. With its limitations, Twitter doesn't provide good user interface in the case of traffic condition. In this paper, information extraction technique is used to get the data of traffic, so that the traffic information can be presented in map view as a mobile application of Android. Natural Language Processing can be used to extract information from a tweet. A tweet will be tokenized, then each of the token will be assigned to a particular part-of-speech tag while analyzing the sentence by using rule based approach. Based on the rules, information of traffic can be extracted in the form of template which consist of time, origin, destination and condition. By using Google Map, the extracted information will be presented in 3 different colors for 3 different levels of traffic condition. Early experiment with limited vocabulary and rules has showed promising result.